PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN GOLDIA CAMILAN MALANG - Andhika Putra Pratama; Agus Widarko; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims 1) to find out how much influence Reward and Punishment simultaneously to employee work motivation, 2) To determine the effect of reward and partial variable of punishment on employee work motivation. The population in this study is the total employee Goldia Camilan Malang, which amounts to 60 employees. The analysis used in this research is multiple linear regression analysis. Based on ststistic test F showed that both variables have influence because it has significance value less than 5% real level. The result of t test shows the significant influence of both variables on employee motivation Goldia Camilan Malang, both have t value> of t table. R square results obtained results of 0.654 means there is a strong relationship between reward and punishment on employee motivation Goldia Camilan Malang. R square of 0.654 which means that reward and punishment in explaining the fluctuation of employee's work motivation variable is 65.4%, while the rest of 34.6% is influenced by factors other than reward and punishmentKeywords: Reward, Punishment, Work Motivation